The Outstanding Natural Landscapes "Vršačke Planine“ in the function of tourism development - Trišić, Igor (The Business of Tourism, 2022)
Protected areas can be important destinations for tourism development because they contribute to economic, environmental and cultural development. In the phase of planning the development of a protected area as a tourism destination, it is important to consider all the possibilities, opportunities, strengths, weaknesses and dangers of tourism implementation, which should be the basic task of management processes. The Outstanding Natural Landscapes "Vršačke Planine“ has significant potential for tourism development. Within this area, there are numerous natural and anthropogenic motives, important for the development of tourism. Favorable geographical location, proximity to major cities in Serbia and the border with Romania, are significant potentials for tourism development in this protected area. In the research in this paper, a quantitative method was used. A total of 250 visitors to this tourism destination was interviewed using the questionnaire survey technique with the help of a questionnaire as a research instrument, the method of random selection. Visitors answered questions about the potential for tourism development of this protected area. The analysis of the respondents' answers concludes that this area has a significant extent of natural factors that contribute to the development of nature-based tourism, such as bird and animal sightseeing, nature photography, health tourism, recreation, science tourism and trips. In addition, the visitors recognized the importance of socio-cultural factors that are important for the development of cultural forms of tourism.
Keywords: protected area; tourism development; Vojvodina; nature-based tourism